Clinicopathological analysis of salivary gland tumors over a 15-year period - Artur Cunha VASCONCELOS; Felipe NÖR; Luise MEURER; Gabriela SALVADORI; Lélia Batista de SOUZA; Pablo Agustin VARGAS; Manoela Domingues MARTINS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Abstract Salivary gland tumors (SGT) are rare neoplasms that generate interest due to their histopathological diversity and clinical behavior. The aims of the present study were to investigate clinicopathological aspects of SGTs diagnosed at a tertiary health center and compare the findings with epidemiological data from different geographic locations. Cases of tumor in the head and neck region at a single health center in the period between 1995 and 2010 were reviewed. Patient gender, age and ethnic group as well as anatomic location, histological type and clinical behavior of the tumor were recorded. Availability of complete information about these aspects was considered the inclusion criteria. Descriptive statistical analysis of the data was performed using the frequencies of categorical variables. Among the 2168 cases of tumors in the head and neck region, 243 (11.20%) cases were diagnosed in the salivary glands, 109 of which met the inclusion criteria: 85 (78%) benign tumors and 24 (22%) malignant tumors. Mean patient age was 46.47 years. The female gender accounted for 56 cases (51.4%) and the male gender accounted for 53 (48.3%). The major salivary glands were affected more (75.2%) than the minor glands. The most frequent benign and malignant SGTs were pleomorphic adenoma (81.2%) and adenoid cystic carcinoma (58.3%), respectively. In conclusion, pleomorphic adenoma and adenoid cystic carcinoma are the most frequent benign and malignant lesions, respectively. Comparing the present data with previous studies on SGTs, one may infer that some demographic characteristics and the predominance of malignant tumors vary in different geographic regions.